THE RESULTS OF STUDYING THE MORPHOLOGY AND BIOLOGY OF THE CAUSATIVE AGENT OF PARAMPHISTOMATOUS DISEASE IN CATTLE (British Journal of Global Ecology and Sustainable Development, 2023)
The article describes the results of studying the morphology and biology of causative agents of paramphistomatous disease in cattle.